Cyclic thermomechanical testing of 316 stainless steel - Buss, T.M.; Hyde, Christopher J. (Taylor & Francis, 2015)
Materials used for components such as power plant steam pipes, gas turbines discs and die forming machinery can be subject to combinations of extreme loading and temperature conditions. In addition, the materials can contain or develop cracks. Once a crack has initiated, the conditions under which the components operate can cause these cracks to propagate. This paper is concerned with the experimental testing of 316 stainless steel, corner cracked samples under thermomechanical fatigue conditions, and the measurement of the crack propagation during testing using alternating current potential difference readings. Fracture mechanics (Paris Law) methods have been used in the processing of the experimental data.